Recurrence risk figures for isolated tetralogy of Fallot after screening for 22q11 microdeletion. Issue 3 (March 1997) - Digilio, M C; Marino, B; Giannotti, A; Toscano, A; Dallapiccola, B
Abstract : Isolated tetralogy of Fallot (TF) has a multifactorial mode of inheritance in most cases, and recurrence risk rates of 2.5-3% have been attributed to first degree relatives of an affected child. In a subgroup of patients with a strong family history, the transmission of a monogenic trait has been suspected. Microdeletion 22q11 (del(22q11)) can cause TF in the setting of DiGeorge and velocardiofacial syndromes, and has also been related to familial conotruncal cardiac defects. Empirical risk figures in families after exclusion of del(22q11) have never been calculated. We have investigated the overall occurrence of congenital heart defect (CHD) in relatives of 102 patients with isolated non-syndromic TF previously screened for del(22q11). Our results show that the frequency of CHD is 3% in sibs, 0.5% in parents, 0.3% in grandparents, 0.2% in uncles or aunts, and 0.6% in first cousins. The recurrence risk rate for sibs in our series is the same as that previously estimated, indicating that after exclusion of patients with del(22q11) genetic counselling to patients with isolated TF should not be modified. A high concordance rate among our affected sibs has been documented. Gene(s) different from those located on chromosome 22q11 must be involved in causing familial aggregation of non-syndromic TF in these cases.